Sensing Molecules with Metal-Organic Framework Functionalized Graphene Transistors - Kumar, Sandeep (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 The Authors. Advanced Materials published by Wiley-VCH GmbH.